Impact of Helicobacter pylori eradication timing on the risk of thromboembolism events in patients with peptic ulcer disease: a population-based cohort study - Cheng-Li Lin; Yen-Chun Peng; Chi-Sen Chang; Jung-Nien Lai; Yi-Jun Liao (BMJ Open, 2022)
Objectives To evaluate the impact of Helicobacter pylori eradication on venous thromboembolism (VTE) events, and the differences between early and late treatment timing.Design A population-based cohort study.Setting Taiwan’s National Health Insurance Research Database.Participants A total of 6736 patients who received H. pylori eradication therapy from 2000 to 2010 were identified. We randomly selected 26 944 subjects matching in gender, age and baseline year as comparison cohort.Primary and secondary outcome measures The incidence rate ratios of VTE in the H. pylori eradication cohorts to that of the control cohort were examined. Multivariable Cox proportional hazard regression analysis was used to estimate the relative HRs and 95% CI of VTE development.Results The total incidence rate of VTE was observed in the late H. pylori eradication cohort, the early H. pylori eradication cohort and the control cohort (15.2, 3.04 and 2.91 per 1000 person-years, respectively). An age-specific trend was found in the late H. pylori eradication cohort, with a greater rate of VTE in the 50–65 years and more than 65 years age groups (adjusted HR 5.44; 95% CI 4.21 to 7.03 and 3.13; 95% CI 2.46 to 3.99). With comorbidities, the late H. pylori eradication cohort seemed to have the highest VTE incidence rate and adjusted HR (4.48, 95% CI 3.78 to 5.30).Conclusions Late H. pylori eradication was associated with a significantly increased risk of VTE, and there was a significantly greater risk of VTE in patients with female gender, age more than 50 years and with comorbidities.